Synthesis and comparative performance study of crystalline and partially amorphous nano-sized SnS2 as anode materials for lithium-ion batteries. (1st October 2022) - Glibo, Albina; Eshraghi, Nicolas; Mautner, Andreas; Jahn, Marcus; Flandorfer, Hans; Cupid, Damian M.
Highlights: After 100 cycles, partially amorphous/nano SnS2 exhibits a capacity of 364 mAh g –1 . Li2 S is beneficial for restraining the volume expansion of SnS2 during cycling. The volume expansion of SnS2 depends on particle size in the electrode. Higher volume expansions result in a thickening of the SEI layer. Abstract: A facile, time effective, and energy efficient precipitation reaction method was developed to synthesize amorphous/nano crystalline SnS2 using SnCl4 ·5H2 O and thioacetamide (C2 H5 NS) as Sn and S sources, respectively. As a comparison, nano-crystalline SnS2 was also synthesized via the already established hydrothermal method using the same Sn- and S precursors. The crystal structure, chemical composition, and morphology of both obtained products were characterized by X-ray diffraction, scanning electron microscopy, transmission electron microscopy and X-ray photoelectron spectroscopy. The electrochemical performance properties of the as-synthesized SnS2 samples were investigated using galvanostatic cycling with potential limitation, cyclic voltammetry, electrochemical impedance spectroscopy and electrochemical in-situ dilatometry. The results show that SnS2 prepared via the precipitation reaction method electrochemically outperforms that from the hydrothermal method. This is due to the formation of thicker Li2 S layers on the particle surfaces, which drastically limits the volume expansion of the Sn particles during the alloying reaction with lithium. Graphical abstract: Image, graphical abstract